MON-LB001 Ovulation Induction Results in Altered Growth and Metabolic Dysfunction in Mice Offspring - Harner, Royce (J Endocr Soc, 2020)
Nearly 15% of couples are affected by infertility and a large proportion of individuals will need to use ovulation induction (OI) or assisted reproductive technologies (ARTs) to conceive. Previous studies have shown that offspring conceived by ARTs are predisposed towards increased insulin resistance and glucose intolerance. However, the long-term effects of OI alone on offspring health have not been studied. This rodent study was designed to elucidate the effects of maternal superovulation on offspring growth and development. C57Bl/6 females were either naturally mated (control= C) or super-ovulated (5 IU PMSG; 5IU hCG, OI group) and mated to C57Bl/6 males with one Agouti viable yellow (Avy) allelic mutation. The Avy allele contains an intracisternal A particle whose methylation levels determine expression of the agouti protein which alters coat color and can be used as a phenotypic readout for global methylation. Offspring (n= 108 control and n = 69 OI) were followed through 13 weeks of age to measure birth parameters, growth rate, fasting glucose, GTT, and body composition (EchoMRI). Parametric and non-parametric tests were used as indicated. Only results with p<0.05 are reported. Results: Surprisingly, while litter size was not different (C = 7, OI = 6), superovulated mothers had fewer surviving pups (C=6.5 pups, OI=5 pups). No major differences in coat color frequencies were observed between the two groups, suggesting no changes in DNA methylation. All OI pups had decreased anogenital distance (males C = 2.1mm, OI = 1.7mm; females C = 1.74mm, OI = 1.48mm), while OI female had lower birthweights (C = 1.38g and OI = 1.23g). Starting at four weeks of age, OI male had lower weight compared to control males. As early as 3 weeks, significant differences in fasting glucose levels were noted (C = 162 mg/dL, OI = 149.5mg/dL). Additionally, superovulated males had lower lean mass at 8 weeks of age (tested by EchoMRI: C = 23.6g, OI = 19.3g) and higher insulin levels at 13 weeks (120 min post injection, C = 339 mg/dL, OI = 213 mg/dL).In summary, we found that the process of OI alone has profound effects on offspring development in a sexual dimorphic fashion. Additional studies will be performed up to 30 weeks of age. Funding: R01 HD092267-01to P